2015
DOI: 10.1007/s11295-015-0947-x
|View full text |Cite
|
Sign up to set email alerts
|

Apple fruit texture QTLs: year and cold storage effects on sensory and instrumental traits

Abstract: Postharvest texture change is a fundamental question for fruit growers and breeders as it drives consumer acceptability. To decipher the genetic control of fruit texture, we studied an apple segregating population over 2 years at harvest and after 2 months of cold storage. Texture complexity was dissected in quantitative traits, related to (i) sensory perception of fruit quality and (ii) fruit mechanical properties. Genetic models including storage, genotype and their interaction effects were built. After sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 90 publications
4
14
0
Order By: Relevance
“…The sensory texture of 'Ben Davis' was the worst and it quickly changed to mealiness; its texture parameters were smaller than the other cultivars, and they decreased more rapidly. These results are in agreement with the results of previous studies [20] , that found that the sensory evaluation of fruit quality was closely related to the mechanical properties of the fruits.…”
Section: Textural Parameters and Sensory Evaluationsupporting
confidence: 93%
See 1 more Smart Citation
“…The sensory texture of 'Ben Davis' was the worst and it quickly changed to mealiness; its texture parameters were smaller than the other cultivars, and they decreased more rapidly. These results are in agreement with the results of previous studies [20] , that found that the sensory evaluation of fruit quality was closely related to the mechanical properties of the fruits.…”
Section: Textural Parameters and Sensory Evaluationsupporting
confidence: 93%
“…[9,[17][18][19] The texture of apples goes through obvious changes during storage and the ultrastructure of different apple cultivars varies significantly. [20,21] The texture of apples is not only related to the ultrastructure but also to the structural characteristics of the fruit. The parameters of a texture profile analysis (TPA) can reflect the structural characteristics of fruit.…”
Section: Introductionmentioning
confidence: 99%
“…A new strategy for detecting QTLs (e.g., metaQTL analysis) could also be beneficial. Several QTLs for fruit texture and storability traits have been identified on this chromosome (Ben Sadok et al, 2015;Bink et al, 2014;Chagné et al, 2014;Costa et al, 2010;Kenis et al, 2008;King et al, 2000;Kumar et al, 2013;Kunihisa et al, 2014;Longhi et al, 2013b). Our findings confirm the importance of chr 10 for elucidating the regulatory mechanisms of fruit texture and storability.…”
Section: Other Qtlssupporting
confidence: 82%
“…Eight hybrids (H074, H097, I016, I062, I095, V034, V083 and W029) from the ‘HIVW’ segregate population resulting from the cross between X3259 and X3263 done in our laboratory at INRA Angers [ 112 , 113 ] were grown on 2 experimental plots (PH and P12) connected to the INRA laboratory at Bois l’Abbé domain (INRA, Angers). Fruits were collected from the middle and outside parts of the tree canopy at 60 and 110 days after flowering (DAF), and optimum maturity (Harvest, H).…”
Section: Methodsmentioning
confidence: 99%